2019
DOI: 10.21926/obm.hg.1902016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Viral Liver Disease and Oral Lichen Planus in Patients Who Visited Dental Clinics: A Study by the Ehime Dental Association

Abstract: Background: The association between hepatitis C virus (HCV) infection and oral lichen planus (OLP), an extrahepatic manifestation, is well known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Of the HCV-infected individuals in Japan, it is estimated that about 470,000 visit medical institutions, about 300,000 are unaware that they are infected, and about 250,000–750,000 are aware that they are infected with HCV but do not receive treatment [ 69 ]. We reported that it is possible for dentists to pick out HCV-infected patients from among those who visit dental clinics for the treatment of dental and oral diseases [ 17 , 18 , 70 , 71 ]. The detection of potential HCV-infected patients by dentists as gatekeepers can contribute to the reduction of liver carcinogenesis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the HCV-infected individuals in Japan, it is estimated that about 470,000 visit medical institutions, about 300,000 are unaware that they are infected, and about 250,000–750,000 are aware that they are infected with HCV but do not receive treatment [ 69 ]. We reported that it is possible for dentists to pick out HCV-infected patients from among those who visit dental clinics for the treatment of dental and oral diseases [ 17 , 18 , 70 , 71 ]. The detection of potential HCV-infected patients by dentists as gatekeepers can contribute to the reduction of liver carcinogenesis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study that encourages the identification of patients with untreated hepatitis through dentistry. We conducted prospective studies to determine whether a general dentist could recommend hepatitis testing to patients who visited a dental clinic (88,89). Twelve clinics (n=5,091 patients), including 11 dental clinics in Yamaguchi prefecture and one institution for oral surgery in a hospital in Shimane prefecture, were included in the study by the end of October 2017 (88).…”
Section: Efforts To Identify Untreated Hepatitis Patients Through Denmentioning
confidence: 99%
“…Several untreated hepatitis patients have been identified during routine dental treatment in several parts of Japan in retrospective and prospective studies ( Fig. 2 and Table I ) ( 74 , 88 , 89 ).…”
Section: Efforts To Identify Untreated Hepatitis Patients Through mentioning
confidence: 99%
See 2 more Smart Citations